The concept of teaching the history course for students of noncore specialties - Evdokimov Roman N.; Kindzerskaya Marina A.; Savinchenko Tatiana I. (SHS Web of Conferences, 2021)
This work is aimed at disclosure of features of history teaching in conformity with modernization processes in Russian higher education. The purpose of this concept is quality improvement of historical education and development of cognitive and socially important knowledge, skills and habits of students of noncore specialties (nonhistory students), economy profile first of all. The concept is based on competence and activity approaches to education. The relevance of development of this concept is dictated by high requirements of modern society to quality of history education, increased public interest to facts of Russian and foreign history, development of historical studies, accumulation of new historical knowledge. In the course of this work, the recommendations have been given regarding development of content and education plan of History discipline, which are universal and after certain adaptation can be used by teachers of other humanitarian and social disciplines. A fresh point of view is proposed on historical education as a tool of formation of system thinking of students, creation of consistent concepts of world history process, including the role of Russia and its development as a part of human civilization.